A rare case of gastric duplication cyst in a male paediatric Caucasian patient: a case report. Issue 10 (27th October 2022) - Duvuru, Ruthwik; AlAwadhi, Ahmad; Nawaz, Faisal; Ahmed, Aftab; Jobran, Afnan W M; Zazo, Aya
Abstract: Anywhere in the alimentary canal, you can find a gastric duplication cyst, a spherical muscle formation lined by mucosal membrane. It is an uncommon example of a group of congenital intestinal abnormalities. Gastric cysts typically develop on the stomach's greater curvature. A Caucasian 4-year-old boy came in with his family after experiencing colicky central stomach pain for 2 days, along with vomiting for 4 days, decreased oral intake, a temperature of up to 38.5°C and regular bowel movements. A region of the transverse colon with degraded and inflammatory serosa covered in omentum with black necrotic sections was seen during the procedure.